Feminizm: Geleneksel Uluslararası İlişkiler Teorilerine Alternatif Yaklaşımlar Demeti - Muhittin Ataman (Alternatif Politika)
This study evaluates the meaning of feminism, its brief history and the place of feminist approaches in international relations. In this context, the second section elaborates the emergence of feminism in the field of international relations and its impact on the discipline. Then, the study offers to analyse the critical perspective of the whole feminist approaches towards basic theories with regard to the concepts of international relations. In the third part of the study, various discourses of different feminist approaches (such as liberal, classical marxist, socialist, radical, postmodern, empiricist, and standpoint feminisms) on international relations are examined. In the last part, the views and the critics of various feminist approaches towards basic subjects and sub-disciplines such as international security international political economy, international law and human rights of mainstream international relations are examined.